Influence of bromide on iodate and iodo-trihalomethane formation during chlorination of iodide-containing waters - Criquet, J.; Allard, Sebastian; Salhi, E.; Joll, C.; Von Gunten, Urs; Heitz, A. (2012)
The kinetics of iodate formation during chlorination of iodide-containing waters is a key factor in the formation of iodoorganic compounds. In contrast to bromate, iodate is considered to be non-toxic. A strategy to reduce the formation of potentially toxic iodoorganic compounds could be to ensure the rapid conversion of iodide to iodate. The observed kinetics of oxidation of iodide by chlorine cannot explain the conversion of iodide to iodate typically observed in water treatment. It has been demonstrated in this study that the formation of bromine by oxidation of bromide during chlorination enhances the oxidation of iodide to iodate. The kinetics of oxidation of iodide by bromine were determined to be relatively fast. Oxidation of iodide by bromine was found to depend on the pH, where a maximum of the reaction rate occurred at pH 9.6, which is the mean of the two pKa values of the main species involved in the limiting reaction (HOBr and HOI). The rate was controlled by the reaction of HOBr + IO- under typical drinking water conditions. A kinetic model was formulated which allows demonstration of catalysis of the oxidation reaction of iodide by bromide. Experiments with various natural waters collected in Switzerland and in Western Australia were performed. These waters were diluted or spiked to achieve different levels of dissolved organic carbon (DOC) and different Br-/I- ratios. The rate and efficiency of iodate formation was found to depend on the water quality, mainly the concentration of bromide and the concentration and the type of DOC. Among the disinfection processes, chloramination usually leads to the highest formation of Iodinated disinfection by-products (I-DBPs). In contrast to ozone or chlorine, the formation of iodate does not occur with monochloramine. Prechlorination followed by addition of ammonia is a potential process to mitigate the formation of I-DBPs during chloramination. The formation of iodinated trihalomethanes (I-THMs) was studied during treatment involving prechlorination followed by addition of ammonia. The formation of iodo-THMs and especially iodoform was significantly reduced by increasing the contact time of chlorination and increasing the Br-/I--ratio. In addition, a relatively low formation of brominated and chlorinated THMs was obtained by this process, with a formation significantly lower than the one obtained during the chlorination process. The optimum prechlorination time for minimal I-THM formation depended strongly on the Br- level; it was determined to be at 60% iodide conversion to iodate. The prechlorination method of chloramination thus shows promise as a method to mitigate I-DBP formation, by promoting iodate formation. In addition, the concentration of bromide is among the relevant parameters which should be taken into consideration in the evaluation of the risk of iodinated DBP formation.